(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1852)
Dr. John Alex Smith exhibited a Roman bronze patella found on a farm near the confluence of the Jed Water and the River Teviot. Not counting trace evidence mentioned by Roy and Stuart, the patella was the first material evidence of Roman inhabitation of the immediate area.